Autologus serum in treatment of dry eye disorder:An evaluation - Rashmi Singh, Ashish Gangwar, Sujata Singh, Braham Dev Sharma (Journal of Applied Pharmaceutical Science)
Dry eye syndrome is a common disorder of the tear film in which eye is unable to maintain a healthy layer of tears to coat it. Despite various conventional treatments such as ocular surface lubrication, artificial tears, protective glasses and punctal occlusion many patients continue to have signs and symptoms of dry eye. That's why autologous serum eye drops have been indicated for the treatment of dry eye. Therefore, to evaluate the effectiveness of the autologous serum eye drops in dry eye disorder, a total of 34 eyes of 20 patients were included in this study, who used autologus serum eye drops along with artificial tears. Out of 20 patients, 16 were males and 4 were females with M: F ratio of 4:1. The mean age of the patients was 51.95 years. Evaluations of patients were done before and after treatment in follow up, by determining the subjective and objective scores which showed that after follow up of 2 months all the subjective and objective scores were reduced in 28 eyes but 6 eyes did not show any improvement at follow up of 2 months as they stopped the drops after one month of use because of discomfort.
Keywords: Dry eye,autologus serum,subjective and objective scores.